Enhanced photocatalytic performance of Bi2Fe4O9/graphene via modifying graphene composite. Issue 8 (21st April 2017) - Liu, Pengdong; Sun, Huajun; Liu, Xiaofang; Sui, Huiting; Zhang, Yong; Zhou, Dingguo; Guo, Qinghu; Ruan, Yong
Abstract: Bi2 Fe4 O9 (BFO) is one of the most important photocatalyst materials and its composition with graphene may leave an optimizing effect on the photocatalytic performance. In this paper, reduced graphene oxide (RGO) with various contents is selected to be composited with BFO successfully via one‐step hydrothermal method. A series of BFO‐ x RGO ( x =0, 1.25, 2.50, 3.75, 5, 6.25, and 7.50 wt.%) were prepared and the effects of RGO content on crystalline, light absorption, impedance, and photocatalytic degradation rate of methyl violet (MV) solution are characterized. The entire film samples exhibit enhanced photocatalytic efficiency. Especially, with 5 wt.% RGO content added, the film sample shows the best photocatalytic degradation efficiency with a MV solution degradation rate of 95%. This implies that the composition of RGO allows BFO‐based thin film as an efficient photocatalyst candidate, and as well, the BFO/RGO composite possesses the potential for better use in the related photocatalyst applications.